A Structuration Perspective Of Management Control System: An Indonesian Case Study - Efferin, Sujoko (The International Journal of Accounting and Business Society, 1997)
This case study is aimed at providing description about social construction of management control system employed within an organisation. ln so doing, this study adopts a sociological approach. that is structuration theory proposed by Anthony Giddens: Using ethnography method, it explicitly examines how and why the system is created from the perspective of an organisation particularly in Indonesian context. The result of this study reveals that far from consisting of merely technical. mechanical aspects. the system in practice is'intertwined with the culture of its broader community in constructing the system. This study also reveals that the adoption otsuch a theory may enable a researcher to understand the link between society, organisational members and the design ofÂ  management control system.